Visual insights into personalizing women's running shoes: A consumer psychology perspective - Jie Zhang; Jun Yao; Hefan Hu; Xuecheng Zhao (Acta Psychologica, 2025)
Objective: This paper explores the rising trend of personalization in sports shoe manufacturing within Industry 4.0, focusing on the psychological aspects of color preferences. Methods: We utilized eye-tracking technology in two experiments to analyze consumer preferences for women's running shoes, examining 18 scenarios with three outsole types and six colorways. Results: Findings highlight the significant psychological influence of outsoles and midsoles on visual attention, revealing that Chinese women prefer warmer and neutral tones in midsoles. Additionally, a correlation between customization experience and gaze duration offers insights into psychological dynamics during the personalization process. Conclusions: This study sheds light on the cognitive dimensions of color preferences among Chinese women regarding sports shoes. Understanding these preferences enables designers and manufacturers to address the psychological needs of this demographic, enhancing personalization and our grasp of color psychology's role in design.